Anode Casting Operation, Process Improvements And Anode Quality At The Ilo Refinery - Victor Raul Alarcon (The Minerals, Metals and Materials Society, 2005)
The Ilo Refinery was commissioned in 1975, with a cathode production capacity of 150,000 tpy. In 1994, Southern Perú Copper Corporation (SPCC) purchased the Refinery from Minero Perú SA. Subsequently, in November 1999, Grupo Mexico acquired control of Southern Perú. The anode production facility is located at the Ilo Refinery. A number of effective operating and quality control practices have been developed that have improved anode quality, as well as increasing anode production capacity to 350,000 tpy. These, and other optimization actions have allowed for a current density increase from 213 A/m2 to 275 A/m2, while maintaining current efficiency at 98% and sustaining the high quality of the cathode. The paper will outline the scope of operational practices in the Anode Plant and provide some discussion on the Ilo Smelter modernization project, and the resulting impact on the existing anode plant.